TP53 and MDM2 genetic alterations in non-small cell lung cancer: Evaluating their prognostic and predictive value. (March 2016) - Deben, Christophe; Deschoolmeester, Vanessa; Lardon, Filip; Rolfo, Christian; Pauwels, Patrick
Highlights: Selected genetic alterations in the p53 pathway are valuable prognostic and predictive biomarkers in NSCLC patients. TP53 inactivating mutations and the Pro variant of the Arg72Pro polymorphism induce a worse overall survival and progression free survival in selected NSCLC subgroups and additionally reduce the response to cisplatin-based therapy. The prognostic and predictive role of MDM2 SNP309 is not clear from the currently available data. Abstract: The p53 pathway has been extensively studied for its role in carcinogenesis. Disruption of the pathway occurs in more than half of all cancers, often leading to a worse prognosis for the patient. In recent years several compounds have been successfully developed to target and restore the p53 pathway, either by blocking the MDM2-p53 interaction, restoring wild type conformation of mutant p53, or exploiting the presence of mutant p53 by blocking DNA damage repair pathways. In this review the known data on the role of p53 on prognosis and response to commonly used chemotherapeutics in non-small cell lung cancer is summarized. The focus is on the presence of genetic alterations in the TP53 or MDM2 gene, p53's main negative regulator. In addition, promising therapeutic options will be discussed in relation to specific alterations in the p53 pathway.